Economics of customer's decisions in smart grid. Issue 1 (1st January 2015) - Misra, Sudip; Bera, Samaresh; Obaidat, Mohammad S.
Abstract : In this study, the authors study the problem of allowing customers to use their storage energy, grid energy, as well as privately owned renewable sources of energy. The customer has three options – grid, storage and self‐generated energy, to fulfill the energy requirements. The grid decides real‐time price to maximise its revenue, while ensuring customers' participation depending on three factors – 'demand', 'supply' and 'time of use'. On the other hand, a customer needs to choose strategies on his/her required energy and associated cost, depending on the storage and self‐generated energy, to maximise the pay‐off. They use Markov decision process (MDP) to design this decision making policy of the customer. In such a MDP‐based decision model, a cost‐effective energy management process is established, and, thus, utility of the customers is maximised. Simulation results show that using the proposed approach, the customers decide the strategies to optimise a trade‐off between energy exchange and associated cost. Thus, the utility for customer is increased approximately 60% with the presence of grid, storage and self‐generated energy sources than that of using only grid and storage energy.